2010
DOI: 10.1186/1471-244x-10-36
|View full text |Cite
|
Sign up to set email alerts
|

Systematic monitoring of needs for care and global outcomes in patients with severe mental illness

Abstract: BackgroundIt was hypothesised that the introduction of tools that allow clinicians to assess patients' needs and to negotiate treatment (Cumulative Needs for Care Monitor; CNCM), would be associated with global outcome improvements in patients diagnosed with severe mental illness.MethodsThe CNCM was introduced in one region in South Limburg (the Netherlands) in 1998 (REGION-1998) and in the rest of South Limburg in 2004 (REGION-2004). By comparing these two regions, changes after the introduction of the CNCM c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
(39 reference statements)
1
15
0
Order By: Relevance
“…The most frequent primary diagnoses carried by participants included MDD and schizophrenia. This is consistent with previous literature, which demonstrates that mood and psychotic disorders represent the most common diagnoses substantiating an SMI label (Drukker, van Os, Bak, Campo, & Delespaul, 2010;Grubaugh, Cusack, & Zinzow, 2008). However, the prevalence of schizophrenia in the overall sample (n = 24, 27%) was lower than would be expected for a CMHC population.…”
Section: Descriptivesupporting
confidence: 92%
See 1 more Smart Citation
“…The most frequent primary diagnoses carried by participants included MDD and schizophrenia. This is consistent with previous literature, which demonstrates that mood and psychotic disorders represent the most common diagnoses substantiating an SMI label (Drukker, van Os, Bak, Campo, & Delespaul, 2010;Grubaugh, Cusack, & Zinzow, 2008). However, the prevalence of schizophrenia in the overall sample (n = 24, 27%) was lower than would be expected for a CMHC population.…”
Section: Descriptivesupporting
confidence: 92%
“…Within CMHCs, from which individuals with SMI are most likely to receive services (McAlpine & Mechanic, 2000), it is more often the case that affective and psychotic disorders are described as the primary condition and qualifier for the SMI distinction. Some researchers have investigated the diagnostic enumerations from clinical inventories or chart reviews of persons deemed severely mentally ill and found elevated and sometimes exclusive rates of mood and psychotic disorders (Drukker, van Os, Bak, Campo, & Delespaul, 2010;Grubaugh, Cusack, & Zinzow, 2008). Furthermore, when researchers report their definition of SMI it is usually consistent with CMHC definitions.…”
Section: Defining Smimentioning
confidence: 99%
“…The motivation feedback intervention under study here, although new in it’s emphasis on motivation for treatment as the content of feedback (as opposed to care needs or quality of life), is otherwise fairly similar to previously trialled clinician feedback where it was found that feedback improved SMI patient outcomes in community mental health settings [20-22]. As Self-Determination Theory is the theoretical basis for the intervention, this ensures that the effects (or potentially no effects) of the intervention can be viewed in light of the processes of change proposed by this theory.…”
Section: Methodsmentioning
confidence: 84%
“…In another study conducted among SMI patients receiving community care, where clinicians received feedback on their patients’ care needs, a significant improvement was found in patient satisfaction, but not on psychopathology, social functioning and quality of life [21] when compared to controls. A study conducted in the Netherlands among patients with severe mental illness, found that systematic monitoring of patients’ care needs in combination with feedback provision was associated with global improvement in depression and anxiety symptoms, but not with improvement in manic excitement and positive symptoms [22]. It seems that structured feedback has positive effects on some central outcomes of community mental health care (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We will assess subjective recovery as secondary outcome variables using a generic personal recovery scale, and by using four measures to assess internal stigma, self-esteem and life-goals: The Mental Health Recovery Measure (MHRM) [39, 40] (authorized Dutch translation [41, 42]); the Internal Stigma of Mental Illness (Ismi) [43]; one item of the Quality of Life section of the Cumulative Needs for Care Monitor (CNCM) [44]; and the Self-Esteem Rating Scale-Short Form (SERS-SF) [45]. In line with Muesers’ conceptual framework, we view improving on personal goals as a mediator variable between illness self-management and recovery [1].…”
Section: Methodsmentioning
confidence: 99%